Biological control of Myzus persicae (Hemiptera: Aphididae) through banker plant system in protected crops - Andorno, Andrea Veronica; Lopez, Silvia Noemi (Elsevier, 2018)
Banker plants with Aphidius colemani were tested in greenhouse for control of Myzus persicae on arugula and sweet pepper crops and compared to inoculative releases of parasitoids. Banker plants system consisted of pots of oat (non-crop plant) infested with Rhopalosiphum padi (non-pest herbivore). The non-pest herbivore serves as an alternative host for A. colemani (parasitoid of the target crop pest). In the arugula crop significant differences in the pest population between the two strategies of biological control showed the lowest densities of the pest when introducing the banker plant system. In the sweet pepper crop, there was no difference in the pest population between the two strategies of biological control.